Study of water quality for post-mining extermination, Banjarbaru City - Sofarini, Dini; Agustian, Reza; Yunandar, Yunandar; Hidayah, Rina Nur (Depik, 2023)
Banjarbaru City is one of the regencies/cities in South Kalimantan Province which continues to develop in various sectors, one of which is mining. Among the mining areas that left traces of voids in Banjarbaru include the Lake Seran quarry which was once a sand mining site, as well as the Pumpung quarry which was a diamond mining location. Remains of former mining excavations that are left for a long time will be filled with water which accumulates various substances remaining at the excavation site, especially heavy metals which in general are important parameters and affect water quality. This study aims to examine the quality of ex-mine water in Banjarbaru by focusing on analysis through the Pollution Index (IP) of heavy metal parameters in the waters of the research location. The results obtained are that the ex-mine pits in Lake Seran and Pumpung, Banjarbaru City, have quite good water quality, where most of them are at class 2 quality standards. However, further management is needed to improve water quality at some points that are still not meets class 2 quality standards so that it is included in the category of lightly polluted.Keywords:MiningHeavy MetalsWater QualityPollution Index